PERANAN KONSELING KRISTEN UNTUK MENOLONG REMAJA KRISTEN DALAM MENGHADAPI PERGUMULAN PILIHAN STUDI - Sahara; Matius Bayo Pote (JURNAL PENABIBLOS, 2024)
This research is motivated by the presence of Christian teenagers who have problems in their studies, especially in their study program, is the choice of their parents, while he himself has other options. Because the parents forced him and his parents to pay for it he was forced to live it. So in his study is not comfortable and the results are very disappointing. This study is a case study study of one adolescent (end) who was studying at UKRIM Yogyakarta. The study hypothesizes that 'presumed Christian counseling has a positive role to help Christian youths who face the study choice struggle' and the results of this study prove the hypothesis